Auslegung eines asynchronen Langstatorlinearmotors mit großem Luftspalt als Straßenbahnantrieb - Springmann, Markus (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
The present paper focuses on the concept of a linear motor for tram operation without overhead lines. The type of motor selected is an asynchronous long-stator linear motor without an adjuster. The resulting big air gap is the biggest challenge in design. First, the impacts of the big air gap are studied analytically. Then, an asynchronous long-stator linear motor for driving the tram is designed using the FE method. The simulation models are validated using a linear motor demonstrator.